is antioxidant therapy effective to treat alzheimer’s disease? - A, LLoret; E, Giraldo; J, Viña (Free Radicals and Antioxidants)
Alzheimer’s disease (AD) is a neurodegenerative process associated with oxidative stress. In the past, it was claimed that all neuronal lesions involved in the onset and progression of AD were related to oxidative stress. Today, we know that intracellular amyloid beta (Ab) could play a central role in the pathophysiology of the disease. Ab binds to heme groups in mitochondrial membranes causing electron transport chain impairment and loss of respiratory function. The experimental evidence of such oxidative stress leads to the basis for treatment of AD with antioxidants. Many clinical trials have been developed to clarify whether antioxidants are beneficial in AD treatment. However, the results obtained in no way confirm that antioxidants are an effective AD therapy. More research is necessary to clarify this point.